Winter – the Increment of Spontaneous ICH (Bangladesh Journal of Neurosurgery, 2020)
Background: Spontaneous intracranial haemorrhage (ICH) is defined as intraparenchymal bleeding in the absence of trauma or surgery. Spontaneous ICH is most disabling and deadly type of stroke. Meteorologic factors and seasons on the incidence of spontaneous ICH with ambiguous results.Objectives: To determine whether different seasons had any relationship with the rate of primary intracerebral hemorrhage.Methods: Total of 209 patients were diagnosed as spontaneous ICH and they have been first time reported & admitted in Combined Military Hospital (CMH) Dhaka, between Jan 2017 and December 2018. Males were 146(69.85%), females were 63(30.15%) and were aged between 18 and 95 years old. Diagnosis was based on history, clinical examination and non-contrast Computed Tomography(CT) scan of brain.Results: 209 admitted patients in CMH Dhaka from Jan 2017- Dec 2018 are included in our study who full-fill the criteria. Intracerebral haemorrhage rate among age group less than 55years old being 55(26.31%) and 55 years and above 154(73.69%).There were a significant relationship between different seasons and intracerebral haemorrhage. Intracerebral haemorrhage incidence in winter season 61(29.18%) and late autumn 19(9.09%), out of 209 patients. Among them hypertensive patients were 137(65.55%) and non-hypertensive patient 72(34.45%), 170 (81.33%) were nondiabetic & 39(18.66%) diabetic of total 209 patients.Out of 61 patients in winter; 54 (88.52%) hypertensive patients had large sized haemorrhage.Conclusion: The highest rate of intracerebral haemorrhage during December-January. There is a seasonal variation in patient’s age, incidence among hypertensive patients, size of hemorrhage and more in number in winter season.Bang. J Neurosurgery 2020; 9(2): 130-134